High abundance and diversity of consumers associated with eutrophic areas in a semi-desert macrotidal coastal ecosystem in Patagonia, Argentina - Martinetto, Paulina Maria del Rosario (2010)
Here we evaluated the response to eutrophication in terms of abundance and diversity of flora and fauna in a semi-desert macrotidal coastal system (San Antonio bay, Patagonia, Argentina, 40° 48′ S) where signs of eutrophication (high nutrient concentration, seaweed blooms, high growth rate of macroalgae) have been reported. We compared abundances and species composition of macroalgae, small infaunal and epifaunal invertebrates, and birds associated with tidal channels of the San Antonio Bay subject to contrasting anthropogenic influence. Macroalgae were more abundant and diverse in the channel closer to human activity where nutrient concentrations were also higher. In contrast to what others have observed in eutrophic sites, small invertebrates and birds were also more abundant and diverse in the channel with macroalgal blooms and high nutrient concentration. The large water flushing during the tidal cycle could prevent anoxic or hypoxic events, making the environment suitable for consumers. Thus, this could be a case in which eutrophication supports high densities of consumers by increasing food availability, rather than negatively affecting the survival of organisms.